Method for producing coated electrode active material

The method of treating Ni-rich electrode active materials with Al or Sb compounds and forming a protective coating addresses surface reactions, improving the electrochemical properties and reducing resistive growth in lithium-ion batteries.

JP2025509738APending Publication Date: 2025-04-11BASF SE
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024555121
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-15
Filing Date
2023-03-10
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing Ni-rich electrode active materials in lithium-ion batteries suffer from undesirable reactions at the surface, leading to decomposition of the electrolyte or solvent, which are not effectively addressed by current coating methods, and methods to remove impurities like LiOH or Li2CO3 do not consistently improve the electrochemical properties.

Method used

A method involving the treatment of Ni-rich electrode active materials with an aqueous medium containing Al or Sb compounds, followed by partial water removal, optional heat treatment, and addition of Al or Sb compounds to deposit elements on the surface, culminating in a heat treatment to form a protective coating.

Benefits of technology

The method results in electrode active materials with improved electrochemical properties, specifically reduced resistive growth during cycling, enhancing the performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025509738000001
    Figure 2025509738000001
  • Figure 2025509738000002
    Figure 2025509738000002
  • Figure 2025509738000003
    Figure 2025509738000003
Patent Text Reader

Abstract

1. A method of making a coated cathode active material, comprising the steps of: (a) General formula Li 1+x TM 1-x providing a particulate electrode active material from O2, wherein TM is Ni, and optionally at least one of Co and Mn, and optionally at least one element selected from Al, Mg and Ba, a transition metal other than Ni, Co and Mn, where x is in the range of 0 to 0.2, and at least 50 mol % of the transition metal in TM is Ni; (b) treating the particulate electrode active material with an aqueous medium containing an Al or Sb compound; (c) at least partially removing the water from step (b); (d) optionally, heat treating the mixture from step (c); (e) adding at least one compound selected from compounds of Al or Sb or B, or a heteropolyacid or its respective ammonium or lithium salt, or a salt of Al, Ga, In or Ba, respectively, to the solid material obtained from step (d) or, where applicable, step (c), thereby depositing at least one selected element on the surface of said particulate electrode active material, wherein the element deposited in step (e) is different from the element deposited in step (b), respectively; (f) heat treating the residue obtained from step (e); Includes.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a method for manufacturing a semiconductor device comprising the steps of: (a) General formula Li 1+x TM 1-x providing a particulate electrode active material by O2, wherein TM is a combination according to general formula (I); (Ni a Co b Mn c ) 1-d M d (I) (In the formula, a is in the range of 0.86 to 0.94, b is 0 or in the range of 0.01 to 0.1; c is in the range of 0.01 to 0.1; d is in the range of 0 to 0.1; M is at least one of Al, Mg, Nb, Ti, Mo, W, and Zr; a+b+c=1), and x is in the range of 0 to 0.05; (b) treating the particulate electrode active material with an aqueous medium containing an Al or Sb compound; (c) at least partially removing the water from step (b); (d) optionally, heat treating the mixture from step (c); (e) adding at least one compound selected from compounds of Al or Sb or B to the solid material obtained from step (d) or, where applicable, step (c), thereby depositing at least one selected element on the surface of said particulate electrode active material, wherein the element deposited in step (e) is different from the element deposited in step (b), respectively; (f) heat treating the residue obtained from step (e); The present invention relates to a method for making a coated cathode active material, comprising: [Background technology]

[0002] Lithium-ion secondary batteries are modern devices for storing energy. Many applications have been considered, from small devices such as mobile phones and laptop computers to car batteries and other e-mobility batteries. Various battery components such as electrolytes, electrode materials and separators have important roles in the performance of the battery. Cathode materials have received particular attention. Several materials have been proposed, such as lithium iron phosphate, lithium cobalt oxide, and lithium nickel cobalt manganese oxide. Extensive research has been conducted, but the solutions found so far still leave room for improvement.

[0003] Currently, particular interest is observed in so-called Ni-rich electrode active materials, for example electrode active materials containing 75 mol % or more of Ni with respect to the total TM content.

[0004] One problem with lithium-ion batteries, especially with Ni-rich electrode active materials, is due to undesirable reactions at the surface of the electrode active material. Such reactions can be the decomposition of the electrolyte or the solvent or both. Therefore, attempts have been made to protect the surface without preventing lithium exchange during charging and discharging. Examples are attempts to coat the electrode active material with, for example, aluminum oxide or calcium oxide (see, for example, US 8,993,051).

[0005] Another theory is that the undesired reaction is assigned to free LiOH or Li2CO3 on the surface. Attempts have been made to remove such free LiOH or Li2CO3 by washing the electrode active material with water (see, for example, JP 4,789,066 B, JP 5,139,024 B, and US2015 / 0372300). However, in some cases, it has been observed that the properties of the obtained electrode active material are not improved. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] US 8,993,051 [Patent Document 2] JP 4,789,066 B [Patent Document 3] JP 5,139,024 B [Patent Document 4] US2015 / 0372300 Summary of the Invention [Problem to be solved by the invention]

[0007] The object of the present invention was to provide a method for producing a Ni-rich electrode active material having good electrochemical properties. It was also an object of the present invention to provide a Ni-rich electrode active material having good electrochemical properties, in particular low resistive growth during cycling. [Means for solving the problem]

[0008] Thus, a method as defined at the outset has been found, hereinafter also called the "method of the invention". The method of the invention comprises the following steps: (a) General formula Li 1+x TM 1-x providing a particulate electrode active material by O2, wherein TM is a combination according to formula (I); (Ni a Co b Mn c ) 1-d M d (I) (In the formula, a is in the range of 0.86 to 0.94, b is 0 or in the range of 0.01 to 0.1; c is in the range of 0.01 to 0.1; d is in the range of 0 to 0.1; M is at least one of Al, Mg, Nb, Ti, Mo, W, and Zr; a+b+c=1), and x is in the range of 0 to 0.05; (b) treating the particulate electrode active material with an aqueous medium containing an Al or Sb compound; (c) at least partially removing the water from step (b); (d) optionally, heat treating the mixture from step (c); (e) adding at least one compound selected from compounds of Al or Sb or B to the solid material obtained from step (d) or, where applicable, step (c), thereby depositing at least one selected element on the surface of said particulate electrode active material, wherein the element deposited in step (e) is different from the element deposited in step (b), respectively; (f) heat treating the residue obtained from step (e); Includes.

[0009] The method of the present invention comprises at least five steps (a), (b), (c), (d), (e) and (f), which are also referred to in the context of the present invention as step (a), step (b), step (c), step (d), step (e) and step (f), respectively. Steps (a) to (g) are carried out thereafter. Step (d) is optional. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] In step (a), the process of the present invention comprises reacting a compound of general formula Li 1+x TM 1-x Starting from an electrode active material with O2, where TM comprises Ni, optionally at least one transition metal selected from Co and Mn, and optionally at least one element selected from Al, Mg and Ba, at least 50 mol %, preferably at least 75 mol % of TM is Ni, and x is in the range of 0 to 0.2. Said material is hereinafter also referred to as starting material.

[0011] In one embodiment of the present invention, the starting material has an average particle size (D50) in the range of 3 to 20 μm, preferably 4 to 16 μm. The average particle size can be determined, for example, by light scattering or laser diffraction or electroacoustic spectroscopy. The particles are usually composed of agglomerates from primary particles, and the above particle size refers to the particle size of the secondary particles.

[0012] In one embodiment of the present invention, the starting material is 0.1 to 2.0 m 2 / g. The BET surface area can be determined by nitrogen adsorption after outgassing the sample at 200 °C for 30 minutes and beyond, according to DIN ISO 9277:2010.

[0013] In one embodiment of the present invention, the particulate material provided in step (a) has a moisture content, determined by Karl Fischer titration, in the range of 20 to 2,000 ppm, preferably 50 to 1,200 ppm.

[0014] In one embodiment of the invention, the variable TM corresponds to the general formula (I): (Ni a Co b Mn c ) 1-d M 1 d (I) (wherein a+b+c=1, a is in the range of 0.6 to 0.99, preferably 0.75 to 0.95, and more preferably 0.85 to 0.95; b is 0 or in the range of 0.01 to 0.2, preferably 0.025 to 0.2, and more preferably 0.025 to 0.1; c is in the range of 0 to 0.2, preferably 0.025 to 0.2, and more preferably 0.05 to 0.1; d is in the range of 0 to 0.1, preferably 0 to 0.04; M 1 is at least one of Al, Mg, Ti, Nb, Mo, W and Zr, preferably at least one of Al, Ti, Zr and W).

[0015] In one embodiment of the invention, the variable c is zero and M 1 is Al, and d is in the range of 0.01 to 0.05.

[0016] In one embodiment of the present invention, TM corresponds to general formula (I) where x ranges from 0 to 0.2, preferably from 0 to 0.1, and even more preferably from 0.01 to 0.05.

[0017] In one embodiment of the present invention, TM is Ni 0.6 Co 0.2 Mn 0.2 , Ni 0.7 Co 0.2 Mn 0.1 , Ni 0.8 Co 0.1 Mn 0.1 , Ni 0.83 Co 0.12 Mn 0.05 , Ni 0.89 Co 0.055 Al 0.055 , Ni 0.91 Co 0.045 Al 0.045 and Ni 0.85 Co 0.1 Mn 0.05 is selected from.

[0018] The electrode active material provided in step (a) usually does not contain conductive carbon, i.e., the content of conductive carbon in the starting material is less than 1 mass %, preferably 0.001 to 1.0 mass %, based on the starting material.

[0019] Some elements are ubiquitous. In the context of the present invention, trace amounts of ubiquitous metals such as sodium, calcium, iron or zinc as impurities are not taken into account in the present specification. Trace amounts in this context mean amounts of 0.02 mol % or less relative to the total metal content of the starting material.

[0020] In step (b), the electrode active material provided in step (a) is treated with an aqueous medium, preferably water. The aqueous medium may have a pH value in the range of 2 to 14, preferably at least 3.5, more preferably 5 to 7. The pH value is measured at the start of step (b). During the course of step (b), the pH value is observed to increase to at least 10, for example 11 to 13. In embodiments where the pH value is in the range of 10 to 11 at the start of step (b), the pH value increases to greater than 11 to 13. In embodiments where the pH value is in the range of 3 to less than 10 at the start of step (b), the pH value increases to 11 to 13 during the course of step (b).

[0021] Preferably, the water hardness, in particular calcium, of the aqueous medium used in step (b) is at least partially removed. The use of demineralized water is preferred.

[0022] In one embodiment of the invention, the aqueous medium contains a dissolved or slurried compound selected from compounds of Al or Sb.

[0023] In one embodiment of the present invention, the amount of the Al or Sb compound is in the range of 0.05 to 1.5 mol %, preferably 0.15 to 0.9 mol %, based on TM.

[0024] Examples of Al or Sb compounds used in step (b) are selected from water-soluble and water-insoluble compounds. Examples of water-soluble compounds of Al are Al2(SO4)3, KAl(SO4)2, or Al(NO3)3. "Water-soluble" in this context means a solubility of at least 10 g of Al or Sb compound per liter of water at 25°C.

[0025] In another embodiment, the inorganic compound of Al is water-insoluble. "Water-insoluble" in this context means a solubility of the compound of less than 0.1 g per liter of water at 25°C. Examples include, for example, Al2O3, Al(OH)3, AlOOH, Al2O3·aq, preferably AlOOH and Al2O3.

[0026] Examples of water-insoluble compounds of Sb are Sb(+III) compounds and Sb(+V) compounds. Examples of Sb(+III) compounds are Sb(OH)3, Sb2O3·aq, Sb2(SO4)3, SbOOH, LiSbO2 and Sb2O3. Examples of Sb(+V) compounds are Sb2O5, LiSb3O8, LiSbO3, Li3SbO4, Li5SbO5, Li7SbO6, Sb2O4(Sb(III)Sb(V)O4), and oxyhydroxides of Sb(+V), such as (but not limited to) SbO(OH)3, Sb2O4(OH)2, Sb2O3(OH)4, Sb3O6OH, Sb3O7OH. Sb(OH)3, Sb2O3·aq and Sb2O3 are preferred. Examples of water-soluble compounds are Sb2(SO4)3, SbONO3, and Sb(NO3)3.

[0027] The water-insoluble compound of Al or Sb may be dispersed or slurried in water.

[0028] In the context of the present invention, AlOOH does not necessarily include equimolar amounts of oxide and hydroxide and may be referred to as Al(O)(OH). The same applies mutatis mutandis to SbOOH.

[0029] The respective compounds of Al or Sb used in step (b), in particular Al2O3 and Al(O)(OH), may be pure (≧99.9 mol % Al, based on all metals including Si) or doped with oxides, e.g. La2O3, Ce2O3, titania or zirconia, e.g. in amounts of 0.1-5 mol %.

[0030] More preferred compounds of Al or Sb in step (b) are Al2(SO4)3 and Sb2O3.

[0031] In one embodiment of the present invention, the water-insoluble compound of Al or Sb has an average particle size (D50) in the range of 10 nm to 10 μm, preferably 10 nm to 3 μm. The average particle size (D50) may be determined by image processing such as SEM.

[0032] In another embodiment, the aqueous medium does not contain dissolved or slurried heteropolyacids, or their respective lithium or ammonium salts, or compounds of Sb.

[0033] In one embodiment of the present invention, step (b) is carried out at a temperature in the range of 5 to 85°C, preferably 10 to 60°C.

[0034] In one embodiment of the invention, step (b) is carried out at normal pressure, however, it is preferred to carry out step (b) at elevated pressure, for example at a pressure between 10 mbar and 10 bar above normal pressure, or under suction, for example at a pressure between 50 and 250 mbar below normal pressure, preferably at a pressure between 100 and 200 mbar below normal pressure.

[0035] For example, step (b) can be carried out in a vessel that can be easily drained, e.g., located above a filter device. Such vessels can be filled with the starting material, followed by the introduction of the aqueous medium. In other embodiments, such vessels are filled with the aqueous medium, followed by the introduction of the starting material. In other embodiments, the starting material and the aqueous medium are introduced simultaneously.

[0036] In one embodiment of the present invention, in step (b), the amounts of water and electrode active material have a mass ratio in the range of 1:5 to 1:5, preferably 2:1 to 1:2.

[0037] Step (b) may be supported by a mixing operation, for example by shaking, or especially by stirring or shearing, see below.

[0038] In one embodiment of the invention, step (b) has a duration in the range of 1 minute to 90 minutes, preferably 1 minute to less than 60 minutes. In embodiments where water treatment and water removal in step (b) are performed overlapping or simultaneously, durations of 5 minutes or more are possible.

[0039] In one embodiment of the invention, the treatment according to step (b) and the removal of water according to step (c) are carried out continuously.

[0040] After or during treatment with the aqueous medium according to step (b), the water may be removed by any type of filtration, for example with a band filter or a filter press.

[0041] In one embodiment of the invention, step (c) is initiated at least 5 minutes after the initiation of step (b). Step (c) comprises partially removing water from the treated particulate matter, for example by solid-liquid separation, for example by decantation, or preferably by filtration. Said "partially removing" is also referred to as partially separating.

[0042] In one embodiment of step (c), the slurry obtained in step (b) is discharged directly into a centrifuge, such as a decanter centrifuge or a filter centrifuge, or into a filter device, such as a suction filter or a filter press, or into a belt filter, which is preferably placed directly below the vessel in which step (b) is carried out, after which filtration begins.

[0043] In a particularly preferred embodiment of the present invention, steps (b) and (c) are carried out in a stirred filter apparatus, such as a stirred pressure filter or a stirred suction filter (e.g. German: "Ruehrfilternutsche"). After combining the starting material and the aqueous medium according to step (b), removal of the aqueous medium is started by starting the filtration after a maximum of 5 minutes, preferably after a maximum of 3 minutes, or even immediately thereafter. On a laboratory scale, steps (b) and (c) may be carried out in a Büchner funnel, and steps (b) and (c) may be supported by manual stirring.

[0044] In a preferred embodiment, step (b) is carried out in a filter apparatus, such as an agitated filter apparatus, which allows for agitation of the slurry or filter cake within the filter.

[0045] In one embodiment of the present invention, the removal of water according to step (c) has a duration ranging from 1 minute to 1 hour.

[0046] In one embodiment of the invention, the stirring in step (b), and, where applicable, step (c), is carried out at a speed in the range of 1 to 50 revolutions per minute ("rpm"), preferably 5 to 20 rpm, in another embodiment it is 200 to 400 rpm.

[0047] In one embodiment of the present invention, the filter media may be selected from ceramics, sintered glass, sintered metals, organic polymer films, nonwoven fabrics, and woven fabrics.

[0048] In one embodiment of the present invention, steps (b) and (c) are carried out under an atmosphere having a reduced CO2 content, for example, a carbon dioxide content in the range of 0.01 to 500 ppm by mass, preferably 0.1 to 50 ppm by mass. The CO2 content can be determined, for example, by optical methods using infrared light. It is even more preferred to carry out steps (b) and (c) under an atmosphere having a carbon dioxide content below the detection limit of, for example, an optical method based on infrared light.

[0049] From step (c), a solid residue is obtained, preferably in the form of a wet filter cake. This solid residue, in particular the filter cake, may have a moisture content ranging from 3 to 20% by weight, preferably from 4 to 9% by weight.

[0050] In an optional step (d), water or solvent is at least partially removed from the mixture resulting from step (d), for example by evaporation. In a preferred embodiment of step (d), the water is at least partially evaporated at a temperature in the range of 40 to 250° C. Preferably, the evaporation of water is carried out at 0.1 to 10 mbar ("in vacuum").

[0051] In step (e), at least one compound selected from compounds of B or Al or Sb is added to the solid material obtained from step (d) or, where applicable, from step (c), thereby depositing at least one element selected from Al, Sb or on the surface of said particulate electrode active material, where the element deposited in step (e) is different from the element deposited in step (b) or (d). Such compound may be added as a slurry or solution or as a dry powder, with dry powder being preferred.

[0052] Thus, step (e) is performed on the solid material obtained from step (d), if step (d) is performed. In embodiments where step (d) is not performed, step (e) is performed on the mixture obtained from step (c), if applicable. In embodiments where step (d) is not performed, step (e) is performed on the solid material obtained from step (c).

[0053] Examples of compounds of aluminium added in step (e) are selected from the same as those disclosed in connection with step (c), with water-insoluble compounds of Al and compounds of B being preferred.

[0054] Examples of compounds of boron are B2O3, boric acid (B(OH)3), and lithium borates, such as LiBO2. Boric acid is preferred.

[0055] In one embodiment of the invention, the water-insoluble aluminum compound is dispersed in water and has an average particle size (D50) in the range of 200 nm to 5 μm, preferably 2 to 5 μm, as determined by X-ray diffraction.

[0056] Examples of antimony compounds are Sb(+III) compounds and Sb(+V) compounds. Examples of Sb(+III) compounds are Sb(OH)3, Sb2O3·aq, Sb2(SO4)3, SbOOH, LiSbO2 and Sb2O3. Examples of Sb(+V) compounds are Sb2O5, LiSb3O8, LiSbO3, Li3SbO4, Li5SbO5, Li7SbO6, Sb2O4(Sb(III)Sb(V)O4), and oxyhydroxides of Sb(+V), such as (but not limited to) SbO(OH)3, Sb2O4(OH)2, Sb2O3(OH)4, Sb3O6OH, Sb3O7OH. Sb(OH)3, Sb2O3·aq and Sb2O3 are preferred.

[0057] In one embodiment of the present invention, the amount of the compound of B, Al or Sb is in the range of 0.05 to 1.5 mol %, preferably 0.15 to 0.9 mol %, based on TM.

[0058] When step (e) is performed, a compound or heteropolyacid of Sb, Al or B is selected so that by performing step (e), at least one element selected from Al, Sb and B is deposited on the surface of the particulate electrode active material, and the element deposited in step (e) is different from the elements deposited in steps (b) and (d).

[0059] In one embodiment of the present invention, at least one compound of Al or B or Sb is added as a particulate solid, for example a dry powder. In particular in the embodiment in which step (d) is performed, step (e) is performed by adding the compound of Al or B or Sb as a dry powder. By "dry powder" is meant one having a residual moisture content of 0.1% by weight or less, as determined by Karl Fischer titration.

[0060] Step (e) may be supported by a mixing operation, for example by shaking, or in particular by stirring or shearing or grinding, see below.

[0061] In one embodiment of the invention, step (e) has a duration in the range of 1 minute to 60 minutes, preferably 1 minute to less than 30 minutes. In embodiments in which water treatment and water removal in step (e) are performed overlapping or simultaneously, durations of 5 minutes or more are possible.

[0062] In one embodiment of the invention, step (e) is carried out at a temperature in the range of 10 to 80° C. Room temperature is even more preferred.

[0063] In one embodiment of the invention, step (e) is carried out in an air atmosphere or under an inert gas such as nitrogen. Ambient air is preferred.

[0064] In one embodiment of the invention, steps (c) to (f) are carried out in the same type of vessel, such as an agitated filter apparatus, such as an agitated pressure filter or an agitated suction filter.

[0065] The method of the present invention comprises the subsequent step (g): (g) heat treating the material resulting from step (e).

[0066] In embodiments where the compound(s) of Al or B or Sb are added as an aqueous slurry or solution, step (g) is particularly preferred.

[0067] Step (g) can be carried out in any type of oven, such as a roller hearth kiln, a pusher kiln, a rotary kiln, a pendulum kiln, or in the case of laboratory scale tests, a muffle oven.

[0068] The temperature of the heat treatment in step (g) is in the range of 150 to 900° C., preferably 250 to 700° C., and even more preferably 300 to 650° C. The said temperature refers to the maximum temperature in step (g).

[0069] Without wishing to be bound by any theory, it is hypothesized that by carrying out step (g), boron compounds may react with the remaining lithium compounds to form lithium-B compounds, e.g., LiBO2. Additionally, aluminum compounds may migrate to Al2O3 and lithium may migrate to Li 1+x TM 1-x Extracted from O2, Li 1+x1 TM 1-x1 Assume that O2 and NiOOH are obtained.

[0070] In one embodiment of the present invention, the temperature is increased before reaching the desired temperature of 150-900° C., preferably 250-700° C. For example, the mixture of step (e) is first heated to 350-550° C., then kept constant for a time period of 10 minutes to 4 hours, and then increased to 500-900° C., preferably 500-850° C.

[0071] In one embodiment of the present invention, the heating rate in step (g) is in the range of 0.1 to 10° C. / min.

[0072] In one embodiment of the present invention, step (g) is carried out in a roller hearth kiln, a pusher kiln or a rotary kiln, or a combination of at least two of them. A rotary kiln has the advantage that the homogenization of the material produced therein is very good. In roller hearth kilns and pusher kilns, different reaction conditions for different steps can be set very easily. In laboratory scale experiments, box furnaces, tube furnaces and split tube furnaces can also be used.

[0073] In one embodiment of the present invention, step (g) is carried out in an oxygen-containing atmosphere, such as a nitrogen-air mixture, a noble gas-oxygen mixture, air, oxygen or oxygen-enriched air or pure oxygen. In a preferred embodiment, the atmosphere in step (g) is selected from air, oxygen and oxygen-enriched air. The oxygen-enriched air can be, for example, a 50:50 volumetric ratio of air and oxygen. Other options include a 1:2 volumetric ratio of air and oxygen, a 1:3 volumetric ratio of air and oxygen, a 2:1 volumetric ratio of air and oxygen, and a 3:1 volumetric ratio of air and oxygen. Pure oxygen is even more preferred.

[0074] In one embodiment of the invention, step (g) has a duration ranging from 30 minutes to 5 hours. Preferably, it ranges from 60 minutes to 4 hours. In this context, the cooling time is ignored.

[0075] By carrying out the method of the present invention, electrode active materials with excellent electrochemical properties are obtained. Without wishing to be bound by any theory, it is hypothesized that the decomposition products of the combination of B or Sb or Al compounds (as the case may be) lead to the capture of lithium compounds deposited on the surface of the electrode active material.

[0076] The cathode active materials obtained by the methods of the present invention have many advantages: Cathodes made from such cathode active materials exhibit reduced resistive growth upon cycling.

[0077] A further aspect of the present invention relates to a coated cathode active material (hereinafter also referred to as the cathode active material of the present invention). The cathode active material of the present invention is a compound represented by the general formula Li 1+x1 TM 1-x1 O2, where TM is a combination of metals according to general formula (I) and x1 is in the range of -0.02 to 0.03, and a shell comprising the following components: - lithium-boron oxide compound or B(OH)3, nickel oxyhydroxide, for example NiOOH, and - Aluminum oxide compounds, such as Al2O3, or compounds of Sb.

[0078] In one embodiment of the invention, TM is a combination of metals according to general formula (I): (Ni a Co b Mn c ) 1-d M 1 d (I) (wherein a+b+c=1, a is in the range of 0.6 to 0.99, preferably 0.75 to 0.95, and more preferably 0.85 to 0.95; b is 0 or in the range of 0.01 to 0.2, preferably 0.025 to 0.2, and more preferably 0.025 to 0.1; c is in the range of 0 to 0.2, preferably 0.025 to 0.2, and more preferably 0.05 to 0.1; d is in the range of 0 to 0.1, preferably 0 to 0.04; M 1 is at least one of Al, Mg, Ti, Nb, Mo, W and Zr, preferably at least one of Al, Ti, Zr and W).

[0079] In one embodiment of the invention, the variable c is zero and M 1 is Al, and d is in the range of 0.01 to 0.05.

[0080] In one embodiment of the present invention, TM corresponds to general formula (I) where x ranges from 0 to 0.2, preferably from 0 to 0.1, and even more preferably from 0.01 to 0.05.

[0081] The cathode active material of the present invention further comprises a shell. Lithium-boron oxide compound or B(OH)3, Nickel oxyhydroxide, e.g., NiOOH, and Aluminum oxide compound or Sb compound, preferably aluminum oxide compound Includes.

[0082] The nickel oxyhydroxide can be detected by X-ray diffraction. In one embodiment of the present invention, the molar ratio of Al to B in the shell of the cathode active material of the present invention ranges from 1:10 to 3:1, preferably from 1:7 to 2:3. In one embodiment of the invention, the shell of the cathode active material of the invention has a thickness in the range of 2 to 10 nm as determined by time-of-flight secondary ion mass spectrometry ("TOF-SIMS").

[0083] A further aspect of the present invention relates to electrodes comprising at least one cathode active material of the present invention. These are particularly useful in lithium-ion batteries. Lithium-ion batteries comprising at least one electrode according to the present invention exhibit very good discharge and cycling behavior and good safety behavior.

[0084] In one embodiment of the present invention, the cathode of the present invention comprises (A) at least one cathode active material of the present invention as described above; (B) Carbon in a conductive state; (C) binder, (D) Current collector Contains:

[0085] In a preferred embodiment of the present invention, the cathode of the present invention comprises, based on the sum of (A), (B) and (C), (A) 80 to 98 mass % of a cathode active material; (B) 1 to 17 mass% carbon, (C) 1 to 10 mass % of a binder Contains:

[0086] The cathode according to the invention contains a conductive modified carbon, also called carbon (B) for short. Carbon (B) can be selected from soot, activated carbon, carbon nanotubes, graphene and graphite. Carbon (B) can be added directly during the preparation of the electrode material according to the invention.

[0087] The electrodes according to the invention may contain further components. They may include a current collector (D), for example (but not limited to) an aluminum foil. They may further include a binder material (C), also referred to below as binder (C). The current collector (D) will not be described further here.

[0088] Suitable binders (C) are preferably selected from organic (co)polymers. Suitable (co)polymers, i.e. homopolymers or copolymers, can be selected, for example, from (co)polymers obtainable by anionic, catalytic or free radical (co)polymerization, in particular from polyethylene, polyacrylonitrile, polybutadiene, polystyrene and copolymers of at least two comonomers selected from ethylene, propylene, styrene, (meth)acrylonitrile and 1,3-butadiene. Polypropylene is also suitable. Polyisoprene and polyacrylates are also suitable. Polyacrylonitrile is particularly preferred.

[0089] In the context of the present invention, polyacrylonitrile is understood to mean not only polyacrylonitrile homopolymers but also copolymers of acrylonitrile with 1,3-butadiene or with styrene. Polyacrylonitrile homopolymers are preferred.

[0090] In the context of the present invention, polyethylene refers not only to homopolyethylenes, but also to copolymerized ethylene with at least 50 mol % and up to 50 mol % of at least one further comonomer, such as α-olefins, such as propylene, butylene (1-butene), 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-pentene, and also isobutene, vinyl aromatics, such as styrene, and also (meth)acrylic acid, vinyl acetate, vinyl propionate, C1-C2 copolymers of (meth)acrylic acid. 10-alkyl esters, in particular methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, n-butyl acrylate, 2-ethylhexyl acrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, and also copolymers of ethylene with maleic acid, maleic anhydride and itaconic anhydride. The polyethylene may be HDPE or LDPE.

[0091] In the context of the present invention, polypropylene is understood to mean not only homopolypropylene but also copolymers of propylene with at least 50 mol % copolymerized propylene and up to 50 mol % of at least one further comonomer, such as ethylene, and α-olefins, such as butylene, 1-hexene, 1-octene, 1-decene, 1-dodecene and 1-pentene. The polypropylene is preferably isotactic polypropylene or essentially isotactic polypropylene.

[0092] In the context of the present invention, polystyrene refers not only to homopolymers of styrene, but also to C1-C4 copolymers of acrylonitrile, 1,3-butadiene, (meth)acrylic acid, and (meth)acrylic acid. 10 -alkyl esters, divinylbenzene, in particular 1,3-divinylbenzene, 1,2-diphenylethylene and α-methylstyrene copolymers are also understood to mean.

[0093] Another preferred binder (C) is polybutadiene.

[0094] Other suitable binders (C) are selected from polyethylene oxide (PEO), cellulose, carboxymethyl cellulose, polyimides and polyvinyl alcohol.

[0095] In one embodiment of the invention, the binder (C) has an average molecular weight M ranging from 50,000 g / mol to 1,000,000 g / mol, preferably up to 500,000 g / mol. W The (co)polymers are selected from those having the formula:

[0096] The binder (C) may be a crosslinked or non-crosslinked (co)polymer.

[0097] In a particularly preferred embodiment of the present invention, the binder (C) is selected from halogenated (co)polymers, in particular fluorinated (co)polymers.Halogenated or fluorinated (co)polymers are understood to mean (co)polymers that contain at least one (co)polymerized (co)monomer with at least one halogen atom or at least one fluorine atom per molecule, more preferably at least two halogen atoms or at least two fluorine atoms per molecule.Examples include polyvinyl chloride, polyvinylidene chloride, polytetrafluoroethylene, polyvinylidene fluoride (PVdF), tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), vinylidene fluoride-tetrafluoroethylene copolymer, perfluoroalkyl vinyl ether copolymer, ethylene-tetrafluoroethylene copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer, and ethylene-chlorofluoroethylene copolymer.

[0098] Suitable binders (C) are especially polyvinyl alcohol and halogenated (co)polymers such as polyvinyl chloride or polyvinylidene chloride, especially fluorinated (co)polymers such as polyvinyl fluoride and especially polyvinylidene fluoride and polytetrafluoroethylene.

[0099] The electrode of the present invention may contain 3 to 10 mass % of binder(s) (d) based on the total mass of the component (a), the component (b) and carbon (c).

[0100] A further aspect of the present invention is (1) at least one cathode comprising a cathode active material (A) of the present invention, carbon (B), and a binder (C); (2) at least one anode; and (3) at least one electrolyte A battery or electrochemical cell comprising:

[0101] The embodiment of the cathode (1) has already been described in detail above.

[0102] The anode (2) may contain at least one anode active material, such as carbon (graphite), TiO2, lithium titanium oxide, silicon, or tin. The anode (2) may further contain a current collector, such as a metal foil, such as copper foil.

[0103] The electrolyte (3) may include at least one non-aqueous solvent, at least one electrolyte salt, and optionally additives.

[0104] The non-aqueous solvent for the electrolyte (3) may be liquid or solid at room temperature and is preferably selected from polymers, cyclic or acyclic ethers, cyclic and acyclic acetals, and cyclic or acyclic organic carbonates.

[0105] Examples of suitable polymers are in particular polyalkylene glycols, preferably poly-C1-C4-alkylene glycols and in particular polyethylene glycols, where the polyethylene glycols may contain up to 20 mol % of one or more C1-C4-alkylene glycols.The polyalkylene glycols are preferably polyalkylene glycols with two methyl or ethyl end caps.

[0106] The molecular weight M of suitable polyalkylene glycols, particularly suitable polyethylene glycols, W may be at least 400 g / mol.

[0107] The molecular weight M of suitable polyalkylene glycols, particularly suitable polyethylene glycols, W can be up to 5,000,000 g / mol, preferably up to 2,000,000 g / mol.

[0108] Examples of suitable acyclic ethers are, for example, diisopropyl ether, di-n-butyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, with 1,2-dimethoxyethane being preferred.

[0109] Examples of suitable cyclic ethers are tetrahydrofuran and 1,4-dioxane.

[0110] Examples of suitable acyclic acetals are, for example, dimethoxymethane, diethoxymethane, 1,1-dimethoxyethane and 1,1-diethoxyethane.

[0111] An example of a suitable cyclic acetal is 1,3-dioxane, and especially 1,3-dioxolane.

[0112] Examples of suitable acyclic organic carbonates are dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate.

[0113] Examples of suitable cyclic organic carbonates are compounds according to general formulae (II) and (III) [ka] (In the formula, R 1 , R 2 and R 3 can be the same or different and are selected from hydrogen and C1-C4-alkyl, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl and tert-butyl, preferably R 2 and R 3 (Both cannot be tert-butyl).

[0114] In a particularly preferred embodiment, R 1 is methyl, R 2 and R 3 are each hydrogen or R 1 , R 2 and R 3 are hydrogen.

[0115] Another preferred cyclic organic carbonate is vinylene carbonate of formula (IV).

[0116] [ka]

[0117] Preferably, the solvent or solvents are used in an aqueous state, ie with a water content in the range of 1 ppm to 0.1% by weight, which can be determined, for example, by Karl Fischer titration.

[0118] The electrolyte (3) further comprises at least one electrolyte salt. Suitable electrolyte salts are in particular lithium salts. Examples of suitable lithium salts are LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiC(C n F 2n+1 SO2)3, lithium imide, e.g. LiN(C n F 2n+1 SO2)2 (wherein n is an integer ranging from 1 to 20), LiN(SO2F)2, Li2SiF6, LiSbF6, LiAlCl4, and compounds of the general formula (C n F 2n+1 SO2) t Salt of YLi where t=1 when Y is selected from oxygen and sulfur; when Y is selected from nitrogen and phosphorus, t=2; When Y is selected from carbon and silicon, t=3).

[0119] Preferred electrolyte salts are selected from LiC(CF3SO2)3, LiN(CF3SO2)2, LiPF6, LiBF4, LiClO4, with LiPF6 and LiN(CF3SO2)2 being particularly preferred.

[0120] In a preferred embodiment of the present invention, the electrolyte (3) contains at least one flame retardant. Useful flame retardants may be selected from trialkyl phosphates (wherein the alkyls are different or the same), triaryl phosphates, alkyl dialkyl phosphonates, and halogenated trialkyl phosphates. Preferred are tri-C1-C4-alkyl phosphates (wherein the C1-C4-alkyls are different or the same), tribenzyl phosphate, triphenyl phosphate, C1-C4-alkyl di-C1-C4-alkyl phosphonates, and fluorinated tri-C1-C4-alkyl phosphates.

[0121] In a preferred embodiment, the electrolyte (3) comprises at least one flame retardant selected from trimethyl phosphate, CH3-P(O)(OCH3)2, triphenyl phosphate, and tris-(2,2,2-trifluoroethyl) phosphate.

[0122] The electrolyte (3) may contain 1 to 10 mass % of a flame retardant based on the total mass of the electrolyte.

[0123] In one embodiment of the invention, the battery according to the invention comprises one or more separators (4) by means of which the electrodes are mechanically separated. Suitable separators (4) are polymer films, in particular porous polymer films, which are unreactive towards metallic lithium. Particularly suitable materials for the separators (4) are polyolefins, in particular film-forming porous polyethylene and film-forming porous polypropylene.

[0124] The separator (4) made of polyolefin, particularly polyethylene or polypropylene, may have a porosity in the range of 35 to 45%. The suitable pore size is, for example, in the range of 30 to 500 nm.

[0125] In another embodiment of the present invention, the separator (4) can be selected from PET nonwoven fabrics filled with inorganic particles. Such separators can have a porosity in the range of 40-55%. Suitable pore sizes are, for example, in the range of 80-750 nm.

[0126] The battery according to the invention may further comprise a housing which may have any shape, for example a cube or a cylindrical disk. In one variant, a metal foil configured as a pouch is used as the housing.

[0127] The battery according to the invention offers very good discharge and cycling behaviour, especially with regard to capacity loss, especially at high temperatures (above 45° C., for example up to 60° C.).

[0128] The battery according to the invention may comprise two or more electrochemical cells that are combined with each other, for example connected in series or connected in parallel. A series connection is preferred. In the battery according to the invention, at least one electrochemical cell contains at least one electrode according to the invention. Preferably, in the electrochemical cell according to the invention, the majority of the electrochemical cells contain electrodes according to the invention. Even more preferably, in the battery according to the invention, all electrochemical cells contain electrodes according to the invention.

[0129] The present invention further provides a method for using the battery according to the present invention in equipment, especially mobile equipment.Examples of mobile equipment are vehicles, such as automobiles, bicycles, aircraft, or water vehicles, such as boats or ships.Other examples of mobile equipment are manually operated, such as computers, especially laptops, phones, or powered hand tools, for example in the construction sector, especially drills, battery-powered drivers, or battery-powered staplers.

[0130] The present invention is further illustrated by the following examples. EXAMPLES

[0131] Conventional notation: N-methyl-2-pyrrolidone: NMP.

[0132] Ultra-dry air: Dehumidified air, with a dew point below -30°C and a CO2 content below 50ppm.

[0133] "Vacuum": 0.1 to 10 millibars.

[0134] I. Synthesis of Cathode Active Material I.1 Synthesis of precursors I.1.1 Synthesis of precursor TM-O.1 Deionized water and 6 g ammonia solution per kg water were placed in a stirred tank reactor. The solution was thermostated at 55° C. and the pH value was adjusted to 11.8 by adding aqueous sodium hydroxide solution.

[0135] The coprecipitation reaction was initiated by simultaneously feeding aqueous solutions of transition metal sulfates and sodium hydroxide through a coaxial nozzle at a flow ratio of 1.97 with a total flow rate of 5 hours residence time. The transition metal solution contained Ni, Co and Mn in a molar ratio of 91:4.5:4.5 and a total transition metal concentration of 1.65 mol / kg. The aqueous sodium hydroxide solution was a 25 wt% sodium hydroxide solution and a 25 wt% ammonia solution at a mass ratio of 11. The pH value was maintained at 11.8 by separately feeding the aqueous sodium hydroxide solution. Starting from the start of all feeds, the suspension overflowed continuously. The resulting suspension was filtered, washed with sodium hydroxide and distilled water and dried at 135 °C to obtain the mixed transition metal (TM) oxyhydroxide precursor TM-OH.1. The dried precursor TM-OH.1 was further dehydrated at 475 °C to produce TM-O.1.

[0136] I.1.2 Synthesis of precursor TM-OH.2 Deionized water and 20 g of ammonium sulfate per kg of water were added to a stirred tank reactor. The solution was thermostated at 55° C. and the pH value was adjusted to 12 by adding aqueous sodium hydroxide solution.

[0137] The coprecipitation reaction was started by feeding aqueous solutions of transition metal sulfates and sodium hydroxide simultaneously at a flow ratio of 1.97 with a total flow rate and a residence time of 5 hours. The transition metal solution contained Ni, Co and Mn in a molar ratio of 88:7:5 and a total transition metal concentration of 1.65 mol / kg. The aqueous sodium hydroxide solution was a 25% by weight solution of sodium hydroxide and 25% by weight solution of ammonia in a mass ratio of 17:1. The pH value was maintained at 12 by feeding the aqueous sodium hydroxide solution separately. Starting from the start of all feeds, a continuous overflow of the suspension was started. The resulting suspension was filtered, washed with sodium hydroxide and distilled water, dried at 120 °C in air and sieved to obtain the mixed transition metal (TM) oxyhydroxide precursor TM-OH.2.

[0138] I.2 Conversion of TM-O.1 and TM-OH.2 into cathode active materials I.2.1 Preparation of Basic Cathode Active Material B-CAM.1, Step (a.1) I.2.1.1 Synthesis of Basic Cathode Active Material B-CAM.1 from TM-O.1, Step (a.1) A quantity of 2.5 kg of precursor TM-O.1 was mixed with 1.48 kg of LiOH monohydrate, 35 g of Al2O3, 8 g of TiO2 and 13 g of ZrO2 in a grinding mill or high shear mixer for 15 minutes. The resulting mixture was placed in a sagger and transferred to a muffle furnace. The temperature was increased to 765°C at a rate of 2°C / min under flowing oxygen, held at 765°C for 8 hours, and then naturally cooled under flowing oxygen. The resulting powder was then deagglomerated in a grinder, further deagglomerated in an air classifying mill and sieved through a 325 mesh screen. After deagglomeration, the resulting powder had an average particle size (D50) of 11 μm.

[0139] I.2.1.2 Synthesis of Basic Cathode Active Material B-CAM.4 from TM-O.1, Step (a.2) A quantity of 2.5 kg of precursor TM-O.1 was mixed with 1.48 kg of LiOH monohydrate, 21 g of Al2O3 and 13 g of ZrO2 in a grinding mill or high shear mixer for 15 minutes. The resulting mixture was placed in a sagger and transferred to a muffle furnace. The temperature was increased to 765°C at a rate of 2°C / min under flowing oxygen, held at 765°C for 8 hours, and then naturally cooled to room temperature under flowing oxygen. The resulting powder was then deagglomerated in a grinder and sieved through a 325 mesh screen. After deagglomeration, the resulting powder had an average particle size (D50) of 11 μm.

[0140] I.2.1.3 Synthesis of Basic Cathode Active Material B-CAM.7 from TM-OH.2, Step (a.3) 2.7 kg of dried precursor TM-OH.2 was mixed with 1.29 kg LiOH monohydrate, 8 g Al2O3, 4 g TiO2 and 9 g ZrO2 in a grinding mill or high shear mixer for 15 minutes. The resulting mixture was placed in a sagger and transferred to a muffle furnace. The temperature was increased to 770°C at a rate of 1.2°C / min under oxygen flow, held at 770°C for 10.5 hours, and then naturally cooled under oxygen flow. The resulting powder was then deagglomerated in a grinder and sieved through a 325 mesh screen. After deagglomeration, the resulting powder had an average particle size (D50) of 11 μm.

[0141] I.2.2 Preparation of cathode active material, steps (b) to (f) I.2.2.1 Synthesis of C-CAM.2 Step (b.1): 67 ml of deionized water was placed in a beaker. B-CAM.1 in an amount of 100 g was added. The resulting slurry was stirred at room temperature for 10 minutes, maintaining the slurry temperature at 25° C. during said stirring.

[0142] Step (c.1): The water was then removed by filtration in a filter press, leaving a wet filter cake.

[0143] Step (d.1): The obtained filter cake was dried at 120° C. for 10 hours in ultra-dry air.

[0144] Step (e.1): Then, 0.57 g (0.9 mol) of boric acid was added and mixed with a high-speed mixer at 25.000 rpm to obtain a mixture.

[0145] Step (f.1): The resulting mixture was heat-treated in a muffle furnace under a forced flow of oxygen at 300° C. for 2 hours, and then the resulting powder was sieved through a 45 μm sieve to obtain a comparative cathode active material C-CAM.2.

[0146] I.2.2.2 Synthesis of CAM.3 Step (b.2): A quantity of 100 g of B-CAM.1 was slurried in deionized water (conductivity of water is less than 5 μS / m) under continuous stirring. An aqueous solution of 0.3 mol % (with respect to TM in B-CAM.1) of Al2(SO4)3 was added. The total amount of deionized water used was 67 ml. The resulting slurry was stirred at room temperature for 10 minutes.

[0147] Step (c.2): The water was then removed by filtration in a filter press, leaving a wet filter cake.

[0148] Step (d.2): The obtained filter cake was dried at 120° C. for 10 hours in ultra-dry air.

[0149] Step (e.2): Then, 0.57 g (0.9 mol) of boric acid was added and mixed with a high-speed mixer at 25.000 rpm to obtain a mixture.

[0150] Step (f.2): The resulting mixture was heat-treated in a muffle furnace under a forced flow of oxygen at 300° C. for 2 hours. The resulting powder was then sieved through a 45 μm sieve to obtain the cathode active material CAM.3 of the present invention.

[0151] I.2.2.3 Manufacturing of C-CAM.5 Step (b.3): 67 ml of deionized water was added to a beaker. B-CAM.4 in an amount of 100 g was added. The resulting slurry was stirred at room temperature for 10 minutes, maintaining the slurry temperature at 25° C. during said stirring.

[0152] Step (c.3): The water was then removed by filtration in a filter press, leaving a wet filter cake.

[0153] Step (d.3): The obtained filter cake was dried at 120° C. for 10 hours in ultra-dry air.

[0154] Step (e.3): Then, 0.57 g (0.9 mol) of boric acid was added and mixed with a high-speed mixer at 25.000 rpm to obtain a mixture.

[0155] Step (f.3): The resulting mixture was heat-treated in a muffle furnace under a forced flow of oxygen at 300° C. for 2 hours, and then the resulting powder was sieved through a 45 μm sieve to obtain a comparative cathode active material C-CAM.5.

[0156] I.2.2.4 Synthesis of CAM.6 Step (b.4): A quantity of 100 g of B-CAM.4 was slurried in deionized water (conductivity of water is less than 5 μS / m) under continuous stirring. An aqueous solution of 0.3 mol % (with respect to TM in B-CAM.4) of Al2(SO4)3 was added. The total amount of deionized water used was 67 ml. The resulting slurry was stirred at room temperature for 10 minutes.

[0157] Step (c.4): The water was then removed by filtration in a filter press, leaving a wet filter cake.

[0158] Step (d.4): The obtained filter cake was dried at 120° C. for 10 hours in ultra-dry air.

[0159] Step (e.4): Then, 0.57 g (0.9 mol) of boric acid was added and mixed with a high-speed mixer at 25.000 rpm to obtain a mixture.

[0160] Step (f.4): The resulting mixture was heat-treated in a muffle furnace under a forced flow of oxygen at 300° C. for 2 hours. The resulting powder was then sieved through a 45 μm sieve to obtain the cathode active material CAM.6 of the present invention.

[0161] I.2.2.5 Manufacturing of C-CAM.8 Step (b.5): 67 ml of deionized water was added to a beaker. B-CAM.7 in an amount of 100 g was added. The resulting slurry was stirred at room temperature for 10 minutes, maintaining the slurry temperature at 25° C. during said stirring.

[0162] Step (c.5): The water was then removed by filtration through a filter press, leaving a wet filter cake.

[0163] Step (d.5): The obtained filter cake was dried at 120° C. for 10 hours in ultra-dry air.

[0164] Step (e.5): Then, 0.57 g (0.9 mol) of boric acid was added and mixed with a high-speed mixer at 25.000 rpm to obtain a mixture.

[0165] Step (f.5): The resulting mixture was heat-treated in a muffle furnace under a forced flow of oxygen at 300° C. for 2 hours, and then the resulting powder was sieved through a 45 μm sieve to obtain a comparative cathode active material C-CAM.8.

[0166] I.2.2.6 Synthesis of CAM.9 Step (b.6): A quantity of 100 g of B-CAM.7 was slurried in deionized water (conductivity of water is less than 5 μS / m) under continuous stirring. An aqueous solution of 0.3 mol % (with respect to TM in B-CAM.7) of Al2(SO4)3 was added. The total amount of deionized water used was 67 ml. The resulting slurry was stirred at room temperature for 10 minutes.

[0167] Step (c.6): The water was then removed by filtration through a filter press, leaving a wet filter cake.

[0168] Step (d.6): The obtained filter cake was dried at 120° C. for 10 hours in ultra-dry air.

[0169] Step (e.6): Then, 0.57 g (0.9 mol) of boric acid was added and mixed with a high-speed mixer at 25.000 rpm to obtain a mixture.

[0170] Step (f.6): The resulting mixture was heat-treated in a muffle furnace under a forced flow of oxygen at 300° C. for 2 hours. The resulting powder was then sieved through a 45 μm sieve to obtain the cathode active material CAM.9 of the present invention.

[0171] The results are summarized in Table 1.

[0172] [Table 1]

[0173] The cathode active materials of the present invention each had a shell containing an aluminum compound, a boron compound (191.8 eV), and NiOOH, which can be detected in the XP spectrum (855.8 eV).

[0174] II. Cathode Active Material Testing II.1 Electrode fabrication II.1.1 Electrode preparation, general procedure 1 Positive electrode: PVDF binder (Solef® 5130) was dissolved in NMP (Merck) to make a 8.0 wt% solution. For electrode preparation, the binder solution (2.5 wt%) and carbon black (Li400, 2.5 wt%) were suspended in NMP. After mixing using a planetary centrifugal mixer (ARE-250, Thinky Corp.; Japan), either the inventive cathode active material CAM.3 or CAM.6, or the base-formed cathode active material B-CAM.1 or B-CAM.4, or the comparative cathode active material C-CAM.2 or C-CAM.5 (95 wt%) were added and the suspension was mixed again to obtain a lump-free slurry. The solid content of the slurry was adjusted to 65%. The slurry was coated on Al foil using a KTF-S roll-to-roll coater (Mathis AG). All electrodes were calendered before use. The thickness of the cathode material was 43 μm, with a concentration of 15 mg / cm. 2 All electrodes were dried at 120 °C for 7 h before cell assembly.

[0175] II.1.2 Electrode preparation, general procedure 2 Positive electrode: PVDF binder (Solef® 5130) was dissolved in NMP (Merck) to make a 8.0 wt% solution. For electrode preparation, the binder solution (4 wt%) and carbon black (Li250, 3.5 wt%) were suspended in NMP. After mixing using a planetary centrifugal mixer (ARE-250, Thinky Corp.; Japan), either the inventive cathode active material CAM.9, or the base-formed cathode active material B-CAM.7, or the comparative cathode active material C-CAM.8 (92.5 wt%) were added and the suspension was mixed again to obtain a lump-free slurry. The solid content of the slurry was adjusted to 65%. The slurry was coated on Al foil using a KTF-S roll-to-roll coater (Mathis AG). All electrodes were calendered before use. The thickness of the cathode material was 48 μm, with a concentration of 15 mg / cm. 2 All electrodes were dried at 120 °C for 7 h before cell assembly.

[0176] II.2 Electrolyte production A base electrolyte composition was prepared according to Table 2 below.

[0177] [Table 2]

[0178] II.3 Test cell construction II.3.1 Manufacturing of test cells based on B-CAM.1, C-CAM.2, CAM.3, B-CAM.4, C-CAM.5 or CAM.6 Coin-shaped half-cells (20 mm in diameter, 3.2 mm in thickness) containing the cathode prepared as described in II.1 and lithium metal as the working and counter electrodes, respectively, were assembled and sealed in an Ar-filled glove box. Furthermore, the cathode, anode, and separator were stacked in the order of cathode / separator / anode to fabricate a coin-shaped half-cell. Then, 0.15 mL of EL.1 was introduced into the coin-shaped cell.

[0179] II.3.2 Manufacturing of test cells based on B-CAM.7, C-CAM.8 or CAM.9 Coin-shaped half-cells (20 mm in diameter, 3.2 mm in thickness) containing the cathode prepared as described in III.1.2 and lithium metal as the working and counter electrodes, respectively, were assembled and sealed in an Ar-filled glove box. Furthermore, the cathode, anode, and separator were stacked in the order of cathode / separator / Li foil to fabricate the coin-shaped half-cell. Then, 0.15 mL of EL.2 described above (II.2) was introduced into the coin-shaped cell.

[0180] III. Evaluation of the performance of coin-type half-cells III.1.1 Cycling tests on coin-type half cells according to B-CAM.1, C-CAM.2, CAM.3, B-CAM.4, C-CAM.5 or CAM.6 The battery performance was evaluated using the manufactured coin cell. For the battery performance, the initial capacity and reaction resistance of the cell were measured. The initial performance and cycle were measured as follows: The coin half cell according to II.3.1 was tested in the voltage range of 4.3 V to 2.7 V at room temperature. In the initial cycle, the first lithiation was performed in CC-CV mode, i.e., a constant current (CC) of 0.5 C was applied until 0.05 V was reached. After a rest period of 10 minutes, reductive lithiation was performed at a constant current of 0.05 C up to 2.7 V. The results are summarized in Table 3. In the cycle, the current density was 0.33 C, and the charge / discharge cycle was repeated 50 times.

[0181] III.1.2 Cycle test with B-CAM.7, C-CAM.8 or CAM.9 coin-type half-cell The battery performance was evaluated using the manufactured coin cell. For the battery performance, the initial capacity and reaction resistance of the cell were measured. The initial performance and cycle were measured as follows: The coin half cell according to II.3.1 was tested in the voltage range of 4.35 V to 2.8 V at room temperature. In the initial cycle, the first lithiation was performed in CC-CV mode, i.e., a constant current (CC) of 0.2 C was applied until 0.01 V was reached. After a rest period of 10 minutes, reductive lithiation was performed at a constant current of 0.2 C up to 2.8 V. The results are summarized in Table 3. In the cycle, the current density was 0.5 C, and charging and discharging at 1.0 C were repeated 50 times.

[0182] The reaction resistance increase of the cell was calculated in the following way: After 25 cycles under 0.1C, the coin cell was recharged to 4.3V and the resistance was measured again by electrochemical impedance spectroscopy (EIS). The ratio of the resistance value at the 26th cycle to that at the 2nd cycle is defined as the resistance increase. The results are summarized in Table 3. The relative resistance increase rate [%] is calculated by taking the resistance increase of the cell based on C-CAM.8 as 100%.

[0183] [Table 3]

Claims

1. The following steps: (a) General formula Li 1+x T.M. 1-x O 2 wherein TM is a combination of metals according to general formula (I), (Ni a Co b Mr c ) 1-d M d (I) (wherein a is in the range of 0.86 to 0.94; b is 0 or in the range of 0.01 to 0.1; c is in the range of 0.01 to 0.1; d is in the range of 0 to 0.1; M is at least one of Al, Mg, Nb, Ti, Mo, W, and Zr; a+b+c=1), x being in the range of 0 to 0.05; (b) treating the particulate electrode active material with an aqueous medium containing an Al or Sb compound; (c) at least partially removing the water from step (b); (d) optionally, heat treating the mixture from step (c); (e) adding at least one compound selected from compounds of Al or Sb or B to the solid material obtained from step (d) or, where applicable, step (c), respectively, thereby depositing at least one selected element on the surface of said particulate electrode active material, wherein the element deposited in step (e) is different from the element deposited in step (b), respectively; (f) heat treating the residue obtained from step (e); A method of making a coated cathode active material comprising:

2. The compounds of Al and Sb added in step (b) are AlOOH and Al 2 O 3 , Al 2 (SO 4 ) 3 , and Sb 2 O 3 The method of claim 1 , wherein the compound is selected from the group consisting of

3. In step (b), AlOOH, Al 2 O 3 and Al 2 (SO 4 ) 3 The method according to claim 1 or 2, wherein a compound of Al selected from the group consisting of:

4. 4. The method according to any one of claims 1 to 3, wherein step (f) comprises a calcination step at a maximum temperature in the range of 300 to 700°C.

5. 5. The method according to any one of claims 1 to 4, wherein step (f) comprises a drying step at a maximum temperature in the range of from 40 to 250°C.

6. General formula Li 1+x1 T.M. 1-x1 O 2 and the following components: Lithium-boron oxide compound or B(OH) 3 , Nickel oxyhydroxide, and Aluminum oxide compound or Sb compound A particulate cathode active material having a shell comprising: TM is a combination of metals according to general formula (I); (Ni a Co b Mr c ) 1-d M d (I) (wherein a is in the range of 0.86 to 0.94; b is 0 or in the range of 0.01 to 0.1; c is in the range of 0.01 to 0.1; d is in the range of 0 to 0.1; M is at least one of Al, Mg, Nb, Ti, Mo, W, and Zr; a+b+c=1), and x1 is in the range of −0.02 to 0.

03.

7. 7. The cathode active material of claim 6, wherein the molar ratio of Al to B in the shell ranges from 1:10 to 3:

1.

8. 8. A particulate electrode active material according to claim 6 or 7, wherein the shell has a thickness in the range of 2 to 10 nm as determined by time-of-flight secondary ion mass spectrometry.

9. (A) at least one cathode active material according to claim 6; (B) carbon in a conductive state; and (C) Binder a cathode.

10. Based on the sum of (A), (B), and (C), (A) 80 to 98 weight percent of a cathode active material; (B) 1 to 17% by mass of carbon; (C) 1 to 10% by mass of a binder 10. The cathode of claim 9 comprising:

11. (1) At least one cathode according to claim 9 or 10, (2) at least one anode; and (3) at least one electrolyte 1. A battery or electrochemical cell comprising:

Citation Information

Patent Citations

  • JP4,789,066B

  • JP5,139,024B

  • Nickel composite hydroxide particle and process for producing the same, positive electrode active material for non-aqueous electrolyte secondary battery and process for producing the same, and non-aqueous electrolyte secondary battery

    US20150372300A1

  • Method for covering particles, especially a battery electrode material particles, and particles obtained with such method and a battery comprising such particle

    US8993051B2